PRO DAN KONTRA SERTIFIKASI PERNIKAHAN - Intan Nurrachmi; Neng Dewi Himayasari (Prodi Hukum Keluarga Islam (Ahwal Asy-Syakhsiyyah) Fakultas Syariah Unisba, 2020)
ABSTRACTPre-marriage counseling programs or so-called bride-to-be courses can be organized by the Ministry of Religion, the Office of Religious Affairs or Agencies and Institutions that have been established by the Ministry of Religion. This guidance aims to provide knowledge about Islamic sharia in domestic life in order to reach families who are confident in mawaddah warahmah. This research is motivated by the Decree of the Director General of Islamic Community Guidance Number. 373 of 2017 concerning Technical Guidance for Marriage Guidance for Prospective Brides. In these rules only contain material / technical / managerial without any binding legal substance so that the phenomenon is now the pros and cons of the imposition of pre-marital certificate obligations in the requirements of marriage registration. This research is qualitative research with descriptive normative analysis studies. The approach used in this research is library research and field research, from this research that is as a journal so that it can be a source of reference about the pros and cons polemics of the validity of pre-marital certificates both for writing thesis, theses, papers, and journals as well as enriching teaching materials study at Ahwal Syakhsiyyah study program for students. In addition, the results of this study are expected to be used as a reference and benchmark for law enforcement and the community in assessing policy Keywords : Marriage, Prenuptial Certificate, Islamic Sharia